Between Spanish American «Modernismo» and Avant-garde: The Inca Incursions in The Black Heralds by Vallejo - Ward, Thomas (2020)
Between the Spanish American «modernismo» and avant-garde movements, César Vallejo’s The Black Heralds shows a strong dose of Indigenism, but also provides elements that evoke ancient Tahuantinsuyo, which constitute what may be called Incanism. This paper aims to isolate some of the indigenous referents of The Black Heralds to determine whether they are indigenist (socio-realistic representation), or Incanist (recovery of the Incas). It concludes by defining the indigenous concept in The Black Heralds.